Complete response with anti-PD-L1 antibody following progression on anti-PD-1 antibody in advanced non-small cell lung cancer. Issue 8 (24th August 2020) - Singh, Navdeep; Seetharamu, Nagashree
Abstract : Immune-checkpoint inhibitors (ICI), specifically inhibitors of programmed death ligand-1 (PD-L1) and receptor (PD-1) are the new standard of care for the treatment of patients with advanced non-small cell lung cancer (NSCLC) in front line setting as monotherapy or along with chemotherapy. Many of these agents are also approved for use in subsequent lines of treatment on progression on platinum doublet chemotherapy. Nivolumab, pembrolizumab and atezolizumab are currently approved ICI for advanced NSCLC. To date, no study has reported efficacy and safety of alternate PD-1/PD-L1 inhibitors in patients with NSCLC who have progressed on one ICI. Here, we report a case of a patient with advanced NSCLC who had a complete response to atezolizumab, following progression of disease on platinum doublet chemotherapy and then, nivolumab monotherapy.